Erythrocytes as carriers of immunoglobulin-based therapeutics. (1st January 2020) - Ji, Weihang; Smith, Paige N.; Koepsel, Richard R.; Andersen, Jill D.; Baker, Stefanie L.; Zhang, Libin; Carmali, Sheiliza; Myerson, Jacob W.; Muzykantov, Vladimir; Russell, Alan J.
Abstract: The global and economic success of immunoglobulin-based therapeutics in treating a wide range of diseases has heightened the need to further enhance their efficacy and lifetime while diminishing deleterious side effects. The three most ubiquitous challenges of therapeutic immunoglobulin delivery are their relatively short lifetimes in vivo, the immunologic consequences of soluble antibody-antigen complexes, and the emergence of anti-drug antibodies. We describe the rapid, cell-tolerated chemical engineering of the erythrocyte membrane in order to display any antibody, our model system being the display of anti-Tumor Necrosis Factor (anti-TNFα), on the surface of long-lived red blood cells (RBCs) while masking the antibody's Fc region. We developed four synthetic approaches to generate RBC-Staphylococcal protein A (RBC-SpA) complexes: amino group targeting through N-hydrosuccinidyl ester-functionalized homobifunctional poly(ethylene glycol) (NHS-PEG-NHS), direct thiol group targeting using heterobifunctional NHS-PEG-maleimide (NHS-PEG-MAL), converted thiol targeting using heterobifunctional NHS-PEG-MAL, and click chemistry using heterobifunctional NHS-PEG-azido (NHS-PEG-N3 ) and NHS-PEG-alkyne (NHS-PEG-alk). The RBC-PEG-SpA complexes were formed within minutes, followed by the attachment of over 10 5 antibodies per RBC to the accessible RBC-bound SpA via Fc-Protein A coupling. The RBC-PEG-SpA-antibody arrays were shown to be stable for more than 60 days in PBS and for more than 42 days in serum containing buffer. RBC-PEG-SpA-antibody complexes were shown to remove TNFα from physiological buffer and had similar mechanical properties to unmodified RBCs. Out of the four approaches, the converted thiol method provided the most controlled chemistry and construct stability. We are now ideally positioned to determine the long-term in vivo efficacy of chemically membrane-engineered RBCs to remove antigens, like TNFα, from serum. Statement of significance: The global and economic success of immunoglobulin-based therapeutics in treating a wide range of diseases has heightened the need to further enhance their efficacy and lifetime while diminishing deleterious side effects. The three most ubiquitous challenges of therapeutic immunoglobulin delivery are their relatively short lifetimes in vivo, the immunologic consequences of soluble antibody-antigen complexes, and the emergence of anti-drug antibodies. We describe the rapid, cell-tolerated chemical engineering of the erythrocyte membrane to display any antibody, our model system being the display of anti-Tumor Necrosis Factor (anti-TNFα), on the surface of long-lived red blood cells (RBCs) while masking the antibody's Fc region. Conversion of RBCs into therapeutic delivery vehicles, we argue, would enhance the circulation life of immunoglobulin-based therapeutics while simultaneously evading deleterious immune response. Graphical abstract: Image, graphical abstract